Mobile health-based home rehabilitation education improving early outcomes after anterior cruciate ligament reconstruction: A randomized controlled clinical trial - Guo, Yi; Li, Dai; Wu, Yi-bo; Sun, Xin; Sun, Xin-ying; Yang, Yu-ping (Frontiers in Public Health, 2023)
Objective: This study aimed to assess changes in joint range of motion and knee joint function between patients who received Mhealth intervention and patients who received regular care at 2 and 6 weeks after ACL reconstruction, in order to provide better interventions in the future. Methods: Patients who underwent ACL reconstruction were randomized into the experimental (mHealth intervention [MHI]; n = 62) and control (CON) groups (n = 63). The CON group underwent home-based rehabilitation exercise in accordance with the paper rehabilitation schedule, while the intervention group received additional Mhealth based education at weeks 1–6 after surgery. Range of motion (ROM), thigh circumference difference, and bent-knee pain were assessed as the primary outcomes. The secondary outcomes were the international knee documentation committee knee evaluation form (IKDC) scores and rehabilitation compliance scores. All the outcomes were measured 1 day prior to surgery as references and at 2 and 6 weeks after surgery. Results: There was no statistical difference in the ROM, thigh circumference difference, and VAS scores of the patients at the 2-week follow-up. At the 6-week follow-up, the range of motion of the affected leg was (118.1±20.5)° in the CON group and (126.6±20.5)° in the MHI group, and the difference was statistically significant (P=0.011). The difference in thigh circumference was 3.0 (2.0, 3.5) cm in the CON group and 2.5 (1.0, 3.0) cm in the MHI group. The difference was statistically significant (P<0.001). The VAS score in the CON group was 3.0 (2.0, 4.0), and the MHI group was 2.5 (1.0, 3.0), the difference was statistically significant (P<0.05). At the 6-week follow-up, the compliance score of patients in the MHI group was significantly higher than that in the CON group (P=0.047, =2.243, 95%CI: 0.026~4.459). There is no statistically significant difference in IKDC scores. Conclusion: Mhealth intervention had a positive effect on patients undergoing ACL reconstruction surgery, particularly in terms of improving the clinical outcome indicators of the knee joint.